ENLIGHTENING THE ROLE OF SAMANYA AND VISESA SIDDHANTA IN CHIKITSA ASPECT - sangdala, *Rekha; Bajpai, Mona; Malik, Meenakshi; Shivudu, K.Venkat (International Journal of Ayurveda and Pharma Research, 2016)
Ayurveda is a science of life. It says, one has to strictly follow the regimens and dietary habits advocated in Samhitas, the classical Ayurvedic texts, to achieve long and healthy life. Any sort of deviation from these principles will lead to the manifestation of disease. According to Ayurveda, the basis for disease manifestation is either Vriddhi or Kshaya of Doshas, and bringing back to normalcy of these Doshas leads to the restoration of health. This process of bringing normalcy is known as Chikitsa and the basic principle of the Chikitsa is Samanya and Visesa siddhanta. According to this Siddhanta, intake of medicine or food having similar properties to that of our body tissues, will results in the increase and those with opposite properties will results in the decrease of our body tissues. Thus, if a disease is manifested due to the Vriddhi of a Dosha, then to pacify that Vriddha dosha, Dravyas having opposite Guna or Karma should be administered. If a disease is manifested due to the Kshaya of a Dosha, then to nourish that Ksheena dosha, Dravyas having similar Guna or Karma should be administered. This Samanya and Visesa Siddhanta should be followed in a rational way while describing the medicine or diet based on the quantitative and qualitative knowledge of Vriddhi or Kshaya of Doshas. Thus, the Samanya and Visesa Siddhanta plays a crucial role in treating diseases and has become the fundamental principle for Ayurvedic management. He details of this Siddhanta are explained elaborately in full paper.